1993
DOI: 10.1136/gut.34.11.1598
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of targeted chemotherapy with lipiodol and 5-epidoxorubicin compared with symptomatic treatment for hepatoma.

Abstract: Lipiodol injected into the hepatic artery is selectively retained in hepatomas so has been used as a vehicle for cytotoxic drugs. This study compared treatment with 5-epidoxorubicin emulsified in lipiodol and infused into the hepatic artery with symptomatic treatment alone in a randomised trial. Of 136 patients with hepatoma 78 (57%) were not elegible, eight (6%) refused to take part, and 50 entered the trial (chemotherapy: n=25, symptomatic treatment: n=25). The two groups had similar prognostic indices. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 11 publications
1
78
1
1
Order By: Relevance
“…Therefore, further studies should be published to ensure a solid assessment, mainly in reference to therapies with acceptable response rates, such as internal radiation [54][55][56] or arterial chemotherapy. [44][45][46][47][48][49][50] In summary, the present systematic review provides consistent evidence that arterial chemoembolization may benefit a subset of patients with unresectable HCC and thus proposes this therapy as the standard intervention in these cases. The data are relevant for the decision-making process of these patients, who at present do not have any option for cure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, further studies should be published to ensure a solid assessment, mainly in reference to therapies with acceptable response rates, such as internal radiation [54][55][56] or arterial chemotherapy. [44][45][46][47][48][49][50] In summary, the present systematic review provides consistent evidence that arterial chemoembolization may benefit a subset of patients with unresectable HCC and thus proposes this therapy as the standard intervention in these cases. The data are relevant for the decision-making process of these patients, who at present do not have any option for cure.…”
Section: Discussionmentioning
confidence: 97%
“…Several treatments of unresectable HCC, such as immunotherapy with interferon, 78,80 antiandrogen therapy, 65 internal radiation, 55 and arterial 47,52 or systemic chemotherapy, 74,76 have also been evaluated in comparison with conservative management. However, none included a sufficient number of patients to guarantee a robust analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others were unable to show a clear difference, even when compared with untreated historical controls [53]. Some randomized studies have been unable to demonstrate a significant difference in survival between patients receiving chemoembolization and those treated symptomatically [54][55][56]. However, the heterogeneity of approaches to the technique of chemoembolization-with each group using different drugs, various intervals between repeated treatments, and the presence or absence of lipiodol-makes generalization of these results impossible.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…In a randomized trial by Madden et al 25 no difference in tumour response or in survival was observed between patients treated with intraarterial chemotherapy mixed with Lipiodol and those treated conservatively. Ischaemia resulting from embolization is probably the main factor of tumour necrosis after TACE.…”
Section: 23mentioning
confidence: 99%